Country risk and government take in Africa's mining sector - (:unkn) unknown (My University, 2024)
A multinational firm’s decision to invest in a mining project depends on a complex decision-making process that considers the physical and economic characteristics of the mine, the mining tax design, the reliability of the host country’s government in meeting its commitments.... and, consequently, the various risks that condition the expected profitability of the investment. Changes in government policy and/or political institutions could affect the investment behaviour of multinationals, as the risk premium is introduced into any investment project and, therefore, the location decision is influenced by political risk. Governments, which need foreign investments to extract resources, cannot ignore the strategies of multinational firms when defining their mining tax design.
Keywords: African Research